Buccosinusal communication in the region of the upper first premolar – atypical case report (Research, Society and Development, 2022)
Introduction: The oroantral (oroantral) communication is an accident resulting from surgery to remove lesions, installation of implants and dental extractions that can result in local disorders, due to the communication between the maxillary sinus and the oral cavity. Diagnosis is made by Valsalva maneuver, imaging exams or the patient's postoperative complaint. The indicated treatment depends on the extension, degree of complexity and condition of the patient. Among the treatment alternatives is the rotation or sliding of the tissue flap to the alveolar region. The incidence of oroantral communications is greater in the molar region due to the expansion of the maxillary sinus in this region. Thus, communications in the premolar region, especially in the upper first premolar region, are atypical. Objective: The present work aims to report an atypical oroantral communication diagnosed soon after the extraction of a first premolar. Case report: Patient C.F.S, male, 39 years old, underwent extraction of 14 after root fracture (CID 10 – K02.4). During surgery, the communication between the maxillary sinus and the remaining alveolus was diagnosed using the Valsalva maneuver. The patient was treated with a palatal flap to preserve the vestibule fundus for a prosthetic rehabilitation treatment, without complications during recovery. Conclusion: It is necessary for the professional to be aware of the extraction of upper teeth close to the maxillary sinus, especially the premolars, although the involvement of these teeth in the oral-sinusal communication is less common.